Cyberculture, cyborgs and science fiction : consciousness and the posthuman - Haney, William S. (Consciousness, literature & the arts, 2006)
"Addressing a key issue related to human nature, this book argues that the first-person experience of pure consciousness may soon be under threat from posthuman biotechnology. Presented here for the first time, the essential argument of this book is more than a warning; it gives a direction: far better to practice patience and develop pure consciousness and evolve into a higher human being than to fall prey to the Faustian temptations of biotechnological power. As argued throughout the book, each person must choose for him or herself between the technological extension of physical experience through mind, body and world on the one hand, and the natural powers of human consciousness on the other as a means to realize their ultimate vision."--Jacket.